Educational games: training of community healthcare agents on children's respiratory diseases - Andrade,Raquel Dully (2008)
OBJECTIVE: Evaluating the use of an educational game about children's respiratory diseases by community healthcare agents (CHAs) in the Family Health Program. METHODS: This is a descriptive, intervention study, with the application of the game to 101 CHAs in Passos-MG. The game was structured with cases of children and families and their respective answer sheets. For evaluation, a test about the topic was applied before and after the intervention. RESULTS: Correct answers in the test increased from 59.5% to 79.3% after participating in the game, which corresponds to a 20% increase. CONCLUSION: The increase in the CHA's knowledge, revealed after the intervention, indicates that the educational game is a satisfactory instrument for healthcare education.